The Curiosity - Kiernan, Stephen (New York : William Morrow, 2013)
After discovering the body of a man buried deep in the Arctic ice, Dr. Kate Philo and her team bring him back to life in their Boston lab, igniting a media firestorm that forces them to decide how far they are willing to go to protect their experiment.
Keywords: Exploitation -- Fiction; Curiosities and wonders -- Fiction; Women scientists -- Fiction; Human experimentation in medicine -- Fiction; Man-woman relationships -- Fiction; Curiosities and wonders -- Fiction; Women scientists -- Fiction; Human experimentation in medicine -- Fiction; Man-woman relationship -- Fiction